2015
DOI: 10.5114/aoms.2015.50966
|View full text |Cite
|
Sign up to set email alerts
|

Renal access through the inferior calyx is associated with higher risk of severe bleeding after percutaneous nephrolithotomy

Abstract: IntroductionHemorrhage is a major complication after percutaneous nephrolithotomy (PCNL). In the current study, we analyzed the risk factors for severe bleeding after PCNL.Material and methodsMedical records of 982 consecutive patients undergoing PCNL at the Department of Urology, the Third Xiangya Hospital, were reviewed. The type of stone included: solitary (n = 471), multiple (n = 192) and staghorn (n = 319). 139 patients had renal stones of solitary kidney or functional solitary kidney. The puncture site w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Several studies have identified prognostic factors for severe bleeding complications after PCNL [ 2 , 3 , 10 , 20 ]. However, due to the absence of standardized reporting classification systems, their results are difficult to interpret and compare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified prognostic factors for severe bleeding complications after PCNL [ 2 , 3 , 10 , 20 ]. However, due to the absence of standardized reporting classification systems, their results are difficult to interpret and compare.…”
Section: Discussionmentioning
confidence: 99%
“…Past analysis of prognostic factors showed that puncture correctness [ 2 ], blood transfusion [ 3 ], puncture via the inferior calyx, and multiple or isolated kidney stones [ 10 ] were previously reported to be independently associated with severe bleeding after PCNL. Severe postoperative bleeding complications are a challenge to urologists and patients.…”
Section: Introductionmentioning
confidence: 99%
“…PCNL was considered to be the best way to tackle large renal stones, regardless of its success rate of operation or its higher SFR [19]- [21]. However, in a large number of recent studies, we have observed that severe complications following PCNL are being reported such as fever, sepsis, hemorrhage requiring blood transfusion and pneumothorax [22], [23] [24]. Lots of scholars reported that some patients are poor medical candidates for PCNL [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…Lower calyceal access requires oblique and longer surgical approaches. To reach the renal pelvis, nephroscope should be adjusted frequently and this increases the risk of laceration of the renal parenchyma (17).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Tan et al (17) reported that severe post-operative bleeding after PCNL wa associated with renal puncture via the lower calyx. multiple renal stones and solitary kidney stones.…”
Section: Discussionmentioning
confidence: 99%